The Development of Emergency Medicine in South Korea: Academic Productivity in Highly Cited Journals. Issue 4 (July 2014) - Lee, J; Kang, HG; Lim, TH; Oh, J; Cho, Y; Cho, JH
Introduction: The purpose of this study was to examine the number of publications by South Korean emergency physicians in highly cited journals and the increase in their numbers. It also sought to assess the impact factors of such publications. Methods: The present study was a retrospective quantitative literature review of the publications by South Korean emergency physicians from 1996 to 2011 in the category of "emergency medicine" in the science edition of Journal Citation Reports 2011. We analysed the total number of articles published by South Korean emergency physicians and their impact factors. Results: Between 1996 and 2011, the number of South Korean board-certified emergency physicians increased from 51 to 958, and 230 articles were published in 14 highly cited journals. The total impact factor (IF) of the original articles published during that period was 227.86, and the mean IF was 1.93. More than 10 articles had been published annually in the past 5 years in highly cited journals and there were over 400 South Korean board-certified emergency physicians. Conclusions: Emergency medicine in South Korea started about 20 years ago, but academic productivity, indicated by at least ten articles annually in highly cited journals, was only achieved in the last five years. The mean IF of these articles was similar to that in other highly productive countries. (Hong Kong j.emerg.med. 2014;21:205-212)